Style components of a coachs management as the effectiveness factor of sports team work - Zheskova, Y. K.; Sharifullina, S. R.; Mutaeva, I. S. (The Russian Journal of Physical Education and Sport, 2019)
The article discusses the experience of studying the relationship between coaches and athletes in team sports. This process should take an important place in a sports team creation and formation. We studied the satisfaction of athletes with the relationship between the coach within their professional activities. The developed judgments made it possible to determine and evaluate in a point system the interrelationships between the style components of the coach`s managerial activity and the relationship with the athlete. We revealed very favorable and quite favorable conditions for the athletes` satisfaction. Research methods. Information sources analysis and summarizing, pedagogical observation, modeling, questionnaire survey methods of mathematical statistics. The research was carried out in 27 youth sports teams of Yelabuga in the following kinds of sports: basketball, volleyball, badminton, table tennis, football. General sampling size was 290 athletes, who had categories. In order to identify the components management style coaches used judgments addressed to athletes. Materials. To identify the effectiveness of the sports team functioning in accordance with modern concepts, we estimated the effectiveness indices of teams and athletes` satisfaction with various aspects of life in the team. The effectiveness of teams was determined by their place in the championship. We created 12 variants of the coach`s management style components, which can be met most often while working with the team. These components are distributed according to the importance presented in the respondents` answers. Results. On the basis of the pedagogical observations and the survey results we created a multi-component model of a coach`s management style. The model includes 12 types of interaction between the coach and the athletes. They characterize the functional aspects of this role. At the same time, we took into consideration formed in psychology notion of management style as stably demonstrated features of interaction between a leader and the team in general and between its separate members. These peculiarities of interaction in "manager-team" system are seen, according to literary data, in the frequency of some functions realization by the manager. They are presented as the components of the coach`s management style. It is assumed that the frequency of the corresponding management style components realization by the coach is an important condition for the effective sports team development. Conclusions. The sports team formation under the guidance of the coach goes through several stages of its formation. In our research work we studied the functioning stages of the existing teams. They reached a certain level of readiness. In order to solve his problem successfuly it is necessary to consider all stages of a sports team development and the satisfaction of athletes at each stage of existence.